2018
DOI: 10.1093/bjsw/bcx142
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Children’s Participation in Decision Making: A Systematic Literature Review Exploring the Effectiveness of Participatory Processes

Abstract: In this article, the term 'participation' refers to the right of the child to express their views in matters affecting them and for their views to be acted upon as appropriate. While there is a growing emphasis in social work practice on a child's right to participate, less attention has been given to how best to support children's participation. A systematic review and narrative synthesis of 20 studies with varying methods explores how effective processes, commonly used in social work practice, are in support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 27 publications
2
42
1
6
Order By: Relevance
“…Thus, further studies need to be conducted to explore what prevents child welfare workers from using full participatory practices with children. As studies in the current article suggest that participation of the child in decision making is dependent on their age, Kennan et al’s (2018) recommendation to study what supports participation of young children in child welfare is very relevant in this context.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 97%
“…Thus, further studies need to be conducted to explore what prevents child welfare workers from using full participatory practices with children. As studies in the current article suggest that participation of the child in decision making is dependent on their age, Kennan et al’s (2018) recommendation to study what supports participation of young children in child welfare is very relevant in this context.…”
Section: Discussion and Concluding Thoughtsmentioning
confidence: 97%
“…As articulated by Hunter and Price‐Robertson (2014, p. 19), ‘child‐inclusive’ approaches are used where adults are the focus of the service, but children have opportunities to directly participate to ‘keep issues of child safety and wellbeing at the centre of policy and practice’. Through a systematic literature review, Kennan, Brady, and Forkan (2018) identify that an organization may improve their effectiveness through providing advocates, having children attendance at meetings and family conferences and using various methods to directly record the child's views. Over recent years, gaining children's perspectives is increasingly being sought through government programme evaluations (such as Queensland's Family and Child Commissioner, 2018) and NGO studies and evaluations to improve practice (Anglicare Southern Queensland, 2017; Leach‐McGill, 2013).…”
Section: Literature Review: Children's Participation In Child and Fammentioning
confidence: 99%
“…Furthermore, research has consistently found that good relationships between professionals and young service users are required to effectively support participation (Gallagher et al, 2012;Archard & Skiveness, 2009;Kennan et al, 2018), and that there is a need to build staff and organisational capacity to balance participative and protectionist practice (Vis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%